Current trends in anesthesia for esophagectomy. Issue 1 (February 2017) - Durkin, Chris; Schisler, Travis; Lohser, Jens
Abstract : Purpose of review: Despite marked improvements in perioperative outcomes, esophagectomy continues to be a high-risk operation associated with significant morbidity and mortality. Progress has been achieved through evidence-based changes in preoperative optimization, intraoperative ventilation strategies, fluid therapy, and analgesia, as well as expedited postoperative recovery pathways. This review will summarize the recent literature on the anesthetic management of patients undergoing esophageal resection. Recent findings: The current focus in publications on the perioperative management of esophagectomy patients can be summarized under the umbrella term of enhanced recovery pathways, focusing on ventilation, fluid therapy, analgesia and minimally invasive surgical approaches. Lung protective ventilation reduces pulmonary complications in cases requiring one-lung ventilation. Excess fluid administration contributes to morbidity while restrictive approaches have not resulted in an increased risk of acute kidney injury. Goal-directed fluid therapy remains intuitive yet unproven. Thoracic epidural analgesia reduces the systemic inflammatory response, pulmonary complications, and enhances postoperative pain control, yet if causing perioperative hypotension may be associated with anastomotic leaks. Enhanced recovery pathways have facilitated low morbidity and mortality rates in a high-risk population but are heterogeneous and limited by a weak evidence base. Minimally invasive surgical approaches are increasingly popular and appear to have at least equivalent outcomes to open procedures. Summary: The morbidity and mortality after esophagectomy remains high despite significant improvements over the last decades. Enhanced recovery pathways appear promising in achieving further marginal gains but at present are lacking large scale, prospective, multicenter evidence.